Development of the Vinylogous Pictet–Spengler Cyclization and Total Synthesis of (±)‐Lundurine A. Issue 23 (4th May 2018) - Nash, Aaron; Qi, Xiangbing; Maity, Pradip; Owens, Kyle; Tambar, Uttam K.
Abstract: A novel vinylogous Pictet–Spengler cyclization has been developed for the generation of indole‐annulated medium‐sized rings. The method enables the synthesis of tetrahydroazocinoindoles with a fully substituted carbon center, a prevalent structural motif in many biologically active alkaloids. The strategy has been applied to the total synthesis of (±)‐lundurine A. Abstract : Not just a happy medium : A vinylogous Pictet–Spengler cyclization has been developed for the generation of indole‐annulated medium‐sized rings. The method enables the synthesis of tetrahydroazocinoindoles with a fully substituted carbon center, a structural motif that is prevalent in biologically active alkaloids. The strategy has been applied to the total synthesis of (±)‐lundurine A (see scheme).